Immunochemical Detection of the Thomsen-Friedenreich Antigen (T-Antigen) on Platelet Plasma Membranes - Glöckner, Wolfgang M; Kaulen, Hermann D; Uhlenbruck, Gerhard (Thrombosis and Haemostasis, 1978)
Platelet plasma membranes were found to possess the disaccharide β--galactosyl(1−3)-N-acetyl-D-galactosamine which was measured by gas chromatography after release by alkaline borohydride treatment and desialylation. Immunological evidence using the specific lectins from Arachis hypogoea and Agaricus bisporus and an anti-T serum confirmed the presence of this disaccharide, the immunodominant group of the Thomsen-Friedenreich antigen (T-antigen). This receptor was only found after prior neuraminidase treatment indicating that it is normally a cryptic antigen, i.e. masked by sialic acid in the native membrane. Evidence for a second receptor with terminal N-acetylgalactosamine was obtained using the lectin from Helix pomatia. The binding of myxovirus and the lectins from Phaseolus vulgaris (PHA) and Canavalia ensiformis (Con A) to platelet membrane was also demonstrated.The implication of the T-antigen in elimination of the platelets and its role in the haemolytic-uraemic syndrome is discussed.